Complex Frontal Pneumosinus Dilatans Associated with Meningioma: A Report of Two Cases and Associated Literature Review - Timms, Sara; Lakhani, Raj; Connor, Steve; Hopkins, Claire (Journal of Neurological Surgery Reports, 2017)
Introduction Pneumosinus dilatans (PSD) is a rare phenomenon involving the expansion of the paranasal sinuses, without bony destruction or a mass. Previously documented cases have demonstrated simple expansion of a solitary air cell. We present two unique cases of PSD in the presence of meningioma, in which complex new cells developed within the frontal sinus. One of the two patients developed associated sinus disease.Case 1 A 28-year-old man presented with facial pain. A computed tomography scan showed an abnormally enlarged, septated right frontal sinus, not present on childhood scans. He underwent a modified endoscopic Lothrop approach to divide the septations, and his symptoms resolved.Case 2 A 72-year-old woman presented with a 3-month history of headaches. Scans revealed a left frontal meningioma and multiple enlarged, dilated left frontal air cells. She had no clinical sinusitis and therefore was managed conservatively.Conclusions PSD has been widely documented in association with fibrous dysplasia and meningioma. The most prevalent theory of the mechanism of PSD is of obstruction of the sinus ostium causing sinus expansion through a “ball-valve” effect. Our cases, which demonstrate septated PSD, suggest a more complex process involving local mediators and highlight the need to consider underlying meningioma in pneumosinus dilatans.
Keywords: pneumosinus dilatans; meningioma; rhinosinusitis; etiology